Overview of the ethical guidelines for medical and biological research involving human subjects in Japan. (29th March 2022) - Eba, Junko; Nakamura, Kenichi
Abstract: The new national guidelines for clinical research, the Ethical Guidelines for Medical and Biological Research Involving Human Subjects, were implemented in Japan in June 2021. The guidelines were developed by integrating two ethical guidelines: Ethical Guidelines for Medical and Health Research Involving Human Subjects and Ethical Guidelines for Human Genome/Gene Analysis Research. The Ethical Guidelines for Clinical Research were originally developed as three separate guidelines: Ethical Guidelines for Human Genome/Gene Analysis Research formulated in 2001, Ethical Guidelines for Epidemiological Research in 2002 and Ethical Guidelines for Clinical Research in 2003. They have undergone several amendments and integration in response to the government's policy changes, such as the protection of personal information, conflicts of interest and reliability of clinical research. The three major changes introduced in the New Integrated Guidelines in 2021 are centralized review, electromagnetic informed consent and research cooperating organization. These are expected to be used as tools to facilitate the conduct of research. This review discusses the regulations of academic clinical research in Japan, the history of ethical guidelines and the three major changes introduced in the New Integrated Guidelines. Abstract : The new ethical guidelines were implemented in 2021. This review discusses the academic clinical research regulations in Japan, the history of ethical guidelines and major changes in the new guidelines.